Epigenetic comparison of CHO hosts and clones reveals divergent methylation and transcription patterns across lineages. Issue 4 (23rd January 2022) - Chang, Meiping; Kumar, Amit; Kumar, Swetha; Huhn, Steven; Timp, Winston; Betenbaugh, Michael; Du, Zhimei
Abstract: In this study, we examined DNA methylation and transcription profiles of recombinant clones derived from two different Chinese hamster ovary hosts. We found striking epigenetic differences between the clones, with global hypomethylation in the host 1 clones that produce bispecific antibody with higher productivity and complex assembly efficiency. Whereas the methylation patterns were found mostly inherited from the host, the host 1 clones exhibited continued demethylation reflected by the hypomethylation of newly emerged differential methylation regions (DMRs) even at the clone development stage. Several interconnected biological functions and pathways including cell adhesion, regulation of ion transport, and cholesterol biosynthesis were significantly altered between the clones at the RNA expression level and contained DMR in the promoter and/or gene‐body of the transcripts, suggesting epigenetic regulation. Indeed, expression changes of epigenetic regulators were observed including writers (Dnmt1, Setdb1), readers (Mecp2), and erasers (Tet3, Kdm3a, Kdm1b/5c) involved in CpG methylation, histone methylation, and heterochromatin maintenance. In addition, we identified putative transcription factors that may be readers or effectors of the epigenetic regulation in these clones. By combining transcriptomics with DNA methylation data, we identified potential processes and factors that may contribute to the variability in cell physiology between different production hosts. Abstract : Epigenetics is an important emerging field in biotechnology. The authors examine DNA methylation and transcription profiles of two different Chinese hamster ovary hosts and the resultant production clones. Combining transcriptomics with DNA methylation data enables identification of potential processes and factors that may contribute to the differences in cell physiology between different production hosts. These differences including epigenetic writers, readers, erasers, and effectors in turn may be important to explaining the variability in productivities of these cell lines.